RESTAURANT SERVICE : PREPARATION CARVING & SLICING FLAMBEING SETTING THE TABLES SERVICE - Boulicot, Thierry; Jeuffrault, Dominique (Nanterre, France : Editions BPI, 2022)
"Covers all the classic techniques and practices of service personnel in fine dining restaurants. Restaurant Service is a comprehensive book that highlights all of the essential dining room service techniques. With this book's guidance, you'll learn how to set the table and how to serve and pour drinks, as well as other forms of table service including slicing and flambéing. Each service technique includes detailed instructions and is illustrated with step-by-step photographs capturing the accuracy and precision of the task. Tracing all the techniques of tableware, Restaurant Service will ensure you have mastered the basics of perfect dining room service and support you throughout your professional journey."-- Provided by publisher
140 Step by step techniques
Keywords: Restaurant management; Restaurants -- Vocational guidance; Food service management